2020
DOI: 10.15452/cejnm.2020.11.0022
|View full text |Cite
|
Sign up to set email alerts
|

Mother-infant bonding in the postpartum period and its predictors

Abstract: Aim: The aim of the study was to assess bonding between a mother and her child with an emphasis on its predictors as well as to identify the women who are at risk of mother-infant bonding disorders. Design: A quantitative cross-sectional study. Methods: To collect the relevant data, the Postpartum Bonding Questionnaire (PBQ) was used to assess the following four factors: quality of mother-infant bond (F1); rejection and pathological anger (F2); infant-focused anxiety (F3); incipient abuse of infant (F4). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
5
3
2
Order By: Relevance
“…In this study, <2% (1.9%) of mothers had incipient abuse of infants (factor-4). This was lower compared to a study done in Slovakia which was 5% ( 17 ). The difference might be sample size, and study setting including differences in the characteristics of study participants and socio-cultural variation.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…In this study, <2% (1.9%) of mothers had incipient abuse of infants (factor-4). This was lower compared to a study done in Slovakia which was 5% ( 17 ). The difference might be sample size, and study setting including differences in the characteristics of study participants and socio-cultural variation.…”
Section: Discussioncontrasting
confidence: 74%
“…Fifty-three (12.6%) mothers have a risk for the general factor which is the quality of mother-infant bond (factor-1) difficulties between mother and an infant. This is higher compared to a study done in Slovakia that identified that 9.5% of women were at-risk in the Factor-1 ( 17 ). Thirty-four (8.1%) of postpartum mothers and 3.6% of postpartum mothers have risk rejection and pathological anger (factor-2) and infant-focused anxiety (factor-3), respectively.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…According to our results, the SSC support has proven to be another significant factor influencing the quality of postpartum MIB. Other studies have confirmed the association between SSC and bond quality (Mazúchová et al, 2020;Phillips, 2013). SSC immediately after birth initiates the early onset of maternal behaviour towards the baby.…”
Section: Discussionmentioning
confidence: 72%